1983
DOI: 10.1002/cne.902150109
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and location of tectal projection neurons in frogs: A study with hrp and cobalt‐filling

Abstract: Tectal projection neurons were labeled by retrograde transport of horseradish peroxidase (HRP) or cobaltic-lysine. The tracer substances were delivered iontophoretically or by pressure injection or diffusion into various regions of the brain or spinal cord. Histochemical procedures allowed identification of labeled cells projecting to the injected regions. Many neurons were filled with cobaltic-lysine, resulting in a Golgi-like staining. After cobalt injections in the diencephalon most of the labeled cells, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…They were activated antidromically by the electric stimulation applied to the pretectal Lpd/P region. Neuroanatomical and some physiological characteristics of the tecto-thalamic projection have been described by others [1,21,[31][32][33] . Our data provide further physiological proof for the existence of reciprocal connections between the tectum and particular pretectal nuclei as suggested by Székely and Lázár [25] .…”
Section: Tecto-pretectal Interactionmentioning
confidence: 86%
See 1 more Smart Citation
“…They were activated antidromically by the electric stimulation applied to the pretectal Lpd/P region. Neuroanatomical and some physiological characteristics of the tecto-thalamic projection have been described by others [1,21,[31][32][33] . Our data provide further physiological proof for the existence of reciprocal connections between the tectum and particular pretectal nuclei as suggested by Székely and Lázár [25] .…”
Section: Tecto-pretectal Interactionmentioning
confidence: 86%
“…Previous immunocytochemical studies [21] have revealed that the pretectal Lpd/P nuclei contain neuropeptide Y (NPY)-like immunoreactivity cells whose fibers distribute in the superficial layers of the ipsilateral tectum (except lamina A), where they partially overlap retinal recipient laminae [22,23] . Because it is known that NPY can reduce the excitatory input, as observed in the rat hippocampus [24] , it is likely that the inhibitory inputs from pretectal cells are attributable to NPY-like immunoreactivity.…”
Section: Pretecto-tectal Information Transfermentioning
confidence: 99%
“…The main target of the tectothalamic projection is the lateral thalamic neuropil (Lázá r et al, 1983;Montgomery and Fite, 1991).…”
Section: Distribution Of Anuran Cartpmentioning
confidence: 99%
“…Cobaltic lysine studies in frogs (Lázár et al, 1983;Antal et al, 1986;Roth et al, 1990) have demonstrated morphological details of projection neurons comparable to those obtained with biocytin but have not produced a complete picture of the number and course of the efferent pathways. In the present study, the use of isolated brain preparations made a locally restricted application of biocytin possible.…”
Section: Indexing Terms: Amphibians; Visual System; Optic Tectum; Tecmentioning
confidence: 86%
“…The latter plays an important role in visual functions of reptiles and birds (Hodos and Karten, 1966;Reiner and Powers, 1978;Powers and Frank, 1983); in mammals it is involved in visual attention (Robinson and Petersen, 1992). It is unclear whether similar tracts projecting to different diencephalic targets exist in amphibians (Lázár et al, 1983).…”
Section: Indexing Terms: Amphibians; Visual System; Optic Tectum; Tecmentioning
confidence: 99%